College physics - Serway, Raymond A.; Faughn, Jerry S. (Belmont, CA : Brooks/Cole, Cengage Learning, 2009)
This text has been revised and updated to include modern physics. Sections deal with problem-solving strategies and include worked example problems and many homework problems.
Includes index.
Keywords: Physics